Gut microbiota: a novel target for exercise-mediated regulation of NLRP3 inflammasome activation - Chen, Jun; Jia, Shaohui; Xue, Xinxuan; Guo, Chenggeng; Dong, Kunwei (Frontiers in Microbiology, 2025)
The NOD-like receptor family pyrin domain-containing 3 (NLRP3) is a key pattern recognition receptor in the innate immune system. Its overactivation leads to the production of pro-inflammatory cytokines, such as IL-1β and IL-18, which contribute to the development and progression of various diseases. In recent years, evidence has shown that gut microbiota plays an important role in regulating the activation of NLRP3 inflammasome. Variations in the function and composition of gut microbiota can directly or indirectly influence NLRP3 inflammasome activation by influencing bacterial components and gut microbiota metabolites. Additionally, exercise has been shown to effectively reduce NLRP3 inflammasome overactivation while promoting beneficial changes in gut microbiota. This suggests that gut microbiota may play a key role in mediating the effects of exercise on NLRP3 inflammasome regulation. This review explores the impact of exercise on gut microbiota and NLRP3 inflammasome activation, and examines the mechanisms through which gut microbiota mediates the anti-inflammatory effects of exercise, providing new avenues for research.